O território nas políticas culturais para as cidades - Albinati, Mariana (Políticas Culturais em Revista, 2010)
Na constituição de territórios interagem fatores de ordem política – poderes atuantes sobre o espaço – e de ordem cultural – valores e significados de que o espaço é investido. O artigo busca apresentar a noção de território, destacando seu aspecto cultural, no sentido de que seja incorporada não apenas aos estudos, mas também, e principalmente, à prática da elaboração das políticas culturais pelo Estado. Apresenta os três principais modelos de políticas culturais democráticas, ressaltando a relação que cada modelo estabelece com o aspecto territorial.PALAVRAS-CHAVE: Território. Política cultural. Espaço cultural.The conception of territory in cultural policies for the citiesABSTRACT: In the constitution of territories interact factors of political order - powers acting on the space – and also from cultural order - values and meanings in which the space is invested by social agents. The paper aims to present the notion of territory, focusing on its cultural aspect, in order to incorporate its notion not only to studies, but also and mainly to the practice of cultural policy development by the state. It presents the three main models of democratic cultural policies, emphasizing the relationship that each model settles with territorial aspect.KEYWORDS: Territory. Cultural policy. Cultural space.